Pengaruh Konsentrasi Pupuk terhadap Pertumbuhan Tanaman Kangkung Darat (Ipomoea reptans. Poir) - Suparno; Mashelin Wulandari (Postgraduate, University of Mataram, 2023)
This study aims to examine the effect of fertilizer concentration on the growth of land kale. The research method chosen was a simple completely randomized design (CRD).The plant samples consisted of 6 groups, each consisting of 5 plants, with 1 group as the control group and the remaining 5 groups as the experimental group. The experimental group was treated with varying concentrations of liquid fertilizer from 2.44% by volume, 4.76% by volume, 6.98% by volume, 9.10% by volume up to 11.11% by volume and observations of plant growth were carried out once every 4 days for 5 period. Based on the plant height results, the experimental group produced the highest average plant in sample E with a concentration of 11.11% by volume. As for the number of leaves parameter, the highest number of leaves was also obtained in the experimental group sample E. Based on the results of analysis of variance using the Anova Test, it was found that the results of Fcount>Ftable were good in the analysis of the effect of fertilizer concentration on plant height and number of leaves. So that the use of liquid fertilizer has a significant effect on the growth of land kale (Ipomea reptans. Poir).